Development of Immunochromatographic Test Strip based on Quantum Dot Nanoparticles (QDs) - T. Sioloetwong (2020)
© Published under licence by IOP Publishing Ltd. Water-soluble fluorescent CdSe/CdZnS quantum dots (QDs) (λem=637nm) were used as a labelling reporter for strip detection. The CdSe/CdZnS QDs was prepared by using core shell technique where CdSe QDs (λem=590nm) core was capped with CdZnS shell. CdZnS-QDs were conjugated with amine-modified DNA probe, that can bio-recognize with DNA product for use in lateral flow assays (LFAs) detection. The presence of functionalized water-dispersible QDs was confirmed by Fourier transform infra-red (FTIR) technique, where a characteristic carboxylic group was observed at 1633 cm-1 (-OH) and 3310 cm-1 (-COO). DNA probe was immobilized onto QDs by EDC/NHS pathways and confirmed by protein absorption spectra at 260 nm due to heterocyclic ring of nucleosides. QDs-DNA can be applied as labelling reporter to readout fluorescence signal on the LFAs detection.